The role of digitization in modernizing the budget of Algerian Public Health Institutions - Hanane, Kada; Fatiha, Bara (The International tax journal, 2026)
This study aims to analyze the impact of digitalization on public finance in the health sector by examining the relationship between the adoption of digital technologies and the efficiency of public resource management. The study employed a descriptive and analytical approach based on official data from the health sector. The results indicate that digitalization improves transparency, rationalizes expenditures, and enhances the effectiveness of public finance. However, the extent of these benefits depends on the readiness of digital infrastructure, the competence of human resources, and the adequacy of the regulatory framework. The study recommends scaling up digital transformation in the health sector to ensure better financial sustainability and higher service quality.